ICMS AND TAXATION ON IMPORTS: CONSTITUTIONALITY, EXTRA-FISCALITY AND PRINCIPLES OF THE WORLD TRADE ORGANIZATION (REMUNOM, 2026)
This article analyzes the use of the Tax on the Circulation of Goods and Services (ICMS) as an extra-fiscal instrument in import operations, evaluating its implications considering the Brazilian constitutional principles of equality, legality, and non-discrimination, as well as Brazil's international commitments to the World Trade Organization (WTO) regarding national treatment and most-favored-nation status. Based on a literature review, analysis of legislation, Supreme Federal Court (STF) decisions, and WTO documents, the constitutionality of increasing ICMS rates on imported goods and their practical effects on the domestic market between 2010 and 2025 was investigated. It was found that, although the ICMS can act as a legitimate instrument of economic policy, its application without clear technical justification and objective criteria produces indirect tax discrimination, violates Article 152 of the Federal Constitution, and exposes the country to potential multilateral disputes. It is concluded that increasing the ICMS (Brazilian state sales tax) on imports is only compatible with domestic law and WTO regulations when parameters of proportionality, transparency, and tax neutrality are observed.